Beautification as Systemic Violence: A Critical Anthropological Perspective - Tahsin, Maria (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to provide a qualitative analysis of the concept of beautification among  university female students, analyzing how systemic violence operates through societal  structures, institutional norms, and media influences on women’s beautification practices. It  also examines the psychological, social, and economic consequences of conformity to beauty  norms. Fieldwork was conducted at Comilla University with female students from various  departments. Both primary and secondary sources were used for data collection. Respondents  were selected using purposive sampling, and a total of 60 participants aged between 20 and 24  years, all currently studying at Comilla University, were interviewed. Qualitative ethnographic  approaches guided the research, and data were collected using multiple techniques. Participant  observation proved effective, allowing the researcher to live within the community and observe  daily life firsthand. The study was further informed by semi-structured interviews, which  combined pre-determined questions with the flexibility to explore emerging themes. Research  tools included field notes and audio recordings, obtained with the consent of each respondent.  Findings reveal that students’ perceptions are conflicted between natural and socially constructed notions of beautification. Beauty norms emerge not from personal preference but  as responses to societal expectations, institutional norms, and media influences. As a result of  these unattainable beauty standards, students experience social rejection, psychological trauma,  and anxiety about unequal job opportunities. This study recommends that policymakers and  researchers critically and effectively address SDG-5 in Bangladesh, advocating for a society  where women are valued for their intellectual competence and aptitude rather than judged by  physical appearance.
Keywords: beautification; systemic violence; patriarchy; women